Analysis of the Effect of Brand Resonance and Brand Trust on Brand Loyalty - Nizarikhutama, Mohammad Bryan; Murwanti, Sri (Jurnal Ilmiah Manajemen Kesatuan, 2024)
Business competition for the products or goods sold. Companies utilize existing resources to obtain superior products. With these resources obtained, you can improve the quality of human resources to meet company needs. The purpose of this research is to analyze whether digital marketing and product quality can influence consumer purchasing decisions on 3Second products in Solo Raya. This research is a quantitative research using a non-probability sampling technique using a purposive sampling method where in this study not all members of the population can be used as a sample, but there are several criteria used so that a person can be used as a sample. The results of this study indicate that digital marketing has no influence on consumer purchasing decisions because it has a t-statistic value <1.96, namely 1.394 and p-values > 0.05, namely 0.164, while product quality has a positive and quite significant influence on purchasing decisions. consumers because it has a t-statistic value > 1.96 which is 6.877 and p-values < 0.05 which is 0.000.